Hubungan Pendidikan Karyawan dengan Tindakan Tidak Aman Bagian Produksi PTP Nusantara VI Rimbo Dua Tebo - Agus Topo Subekti; Yulianto Yulianto (Yayasan Literasi Sains Indonesia, 2023)
The success of the national development of a nation is determined by the availability of quality Human Resources (HR), namely human resources which include physically tough, mentally strong and excellent health, as well as mastery of science and technology. Human resources, including in this case, the workforce must be maintained and their health level improved so that they can live a more productive life. (RI Ministry of Health, 2013: 2). MOH RI (2015: 15) Accidents occur due to lack of awareness of the workforce and inadequate quality and skills of the workforce. Many workers at work underestimate work risks, so they don't use personal protective equipment even though it has been provided by the company. According to the ILO (1999: 15) Work accident is an event that is unexpected and unwanted from the start which disrupts the process of predetermined activities and can result in loss of both lives and property. From the definition of an accident above, it can be concluded that a work accident is an unexpected event and can result in losses either directly or indirectly and interfere with the productivity and work processes of the workforce. After conducting research and statistical tests, the authors finally concluded that there was no relationship between education level and Unsafe Actions at Work in the palm oil production section at PTPN VI (Persero) Rimbo Dua Business Unit, Tebo District in 2019.